The Modern English - Esonov Otabek Chori o’g’li (Journal of Innovation in Education and Social Research, 2025)
This article explores the development and current characteristics of modern English. It traces the historical progression from Middle English to the present day, analyzing the linguistic, technological, and social influences that have contributed to its evolution. Emphasis is placed on vocabulary expansion, grammar simplification, the impact of digital communication, and the emergence of global varieties known as "World Englishes." This study aims to highlight the dynamic and adaptive nature of English as it continues to evolve in response to globalization and technological change. Furthermore, this article examines the evolution and current features of modern English. It explores how historical, technological, and social changes have shaped the language, leading to vocabulary expansion, simplification of grammar, and the emergence of global varieties. The article aims to provide a deeper understanding of the dynamic nature of English in contemporary society.